Historical Study: Jantho City and Infrastructure, 1979-2020 - Khairullah Khairullah; T. Bahagia Kesuma (Riwayat: Educational Journal of History and Humanities, 2022)
Jantho City is the Capital of the Aceh Besar Regency. This study aims to (1) describe the background of the determination of the Janthoi Settlement as the Capital of Aceh Besar District; (2) describe the initial and continued development process of Jantho City infrastructure 1979-2020; and (3) Identification the factors causing the failure of the development of Jantho City to become a new growth center. This study uses a type of approach that is combined with historical methods. The data collection techniques were carried out using documentation, literature study, and interviews. The results of this study are (1) the determination of the Janthoi Settlement as the Capital of Aceh Besar Regency because of its strategic location for regional development and have a very potential back area; (2) initial development in the form of the construction of the main infrastructure of the city, such as government buildings, roads, post offices, mosques, electricity networks, telephone networks, and other facilities for government purposes. Continued development in the form of supporting urban infrastructures, such as education, health, sports, housing, and economic facilities; (3) several factors cause Jantho City to fail to develop, namely its location opposite to other growth centers in Aceh Besar District, only working in the administrative center, not having a long historical background, no interaction with back areas, armed conflict in Aceh, and unsustainable development.